The Behavioral and Neurochemical Effects of a Novel d-Amino Acid Oxidase Inhibitor Compound 8 [4 H-Thieno [3,2-b]pyrrole-5-carboxylic Acid] and d-Serine - Smith, Sean M.; Uslaner, Jason M.; Yao, Lihang; Mullins, Chadwick M.; Surles, Nathan O.; Huszar, Sarah L.; McNaughton, Caitlyn H.; Pascarella, Danette M.; Kandebo, Monika; Hinchliffe, Richard M.; Sparey, Tim; Brandon, Nicholas J.; et al. (The Journal of pharmacology and experimental therapeutics, 2009)
Multiple studies indicate that N-methyl-d-aspartate (NMDA) receptor hypofunction underlies some of the deficits associated with schizophrenia. One approach for improving NMDA receptor function is to enhance occupancy of the glycine modulatory site on the NMDA receptor by increasing the availability of the endogenous coagonists d-serine. Here, we characterized a novel d-amino acid oxidase (DAAO) inhibitor, compound 8 [4 H-thieno [3,2-b]pyrrole-5-carboxylic acid] and compared it with d-serine. Compound 8 is a moderately potent inhibitor of human (IC50, 145 nM) and rat (IC50, 114 nM) DAAO in vitro. In rats, compound 8 (200 mg/kg) decreased kidney DAAO activity by ∼96% and brain DAAO activity by ∼80%. This marked decrease in DAAO activity resulted in a significant (p < 0.001) elevation in both plasma (220% of control) and cerebrospinal fluid (CSF; 175% of control) d-serine concentration. However, compound 8 failed to significantly influence amphetamine-induced psychomotor activity, nucleus accumbens dopamine release, or an MK-801 (dizocilpine maleate)-induced deficit in novel object recognition in rats. In contrast, high doses of d-serine attenuated both amphetamine-induced psychomotor activity and dopamine release and also improved performance in novel object recognition. Behaviorally efficacious doses of d-serine (1280 mg/kg) increased CSF levels of d-serine 40-fold above that achieved by the maximal dose of compound 8. These findings demonstrate that pharmacological inhibition of DAAO significantly increases d-serine concentration in the periphery and central nervous system. However, acute inhibition of DAAO appears not to be sufficient to increase d-serine to concentrations required to produce antipsychotic and cognitive enhancing effects similar to those observed after administration of high doses of exogenous d-serine.